Medical Robot Systems Used in Clinical Practice - Nodirbek Kimsanboev (Genius Journals, 2023)
Medical robot systems have revolutionized the healthcare industry, offering precise and accurate assistance to healthcare professionals in clinical practice. This thesis focuses on the use of medical robot systems in clinical practice. The thesis covers various aspects of medical robots such as their applications, advantages, and limitations. The thesis will also delve into the different types of medical robot systems, including surgical robots, rehabilitation robots, and telepresence robots. Additionally, the thesis will explore the ethical considerations surrounding the use of medical robots in clinical practice, including patient safety, privacy, and confidentiality. Overall, this thesis provides a comprehensive overview of the use of medical robot systems in clinical practice, highlighting their benefits and limitations, and ethical considerations.
Keywords: Medical robot; surgical robots; rehabilitation robots; telepresence robots